Pre-existing TGF-β-specific T-cell immunity in patients with pancreatic cancer predicts survival after checkpoint inhibitors combined with radiotherapy - Mads Hald Andersen; Özcan Met; Inge Marie Svane; Morten Orebo Holmström; Thomas Landkildehus Lisle; Rasmus Erik Johansson Mortensen; Jane P Hasselby; Gro L Willemoe; Julia Johansen; Dorte L Nielsen; Inna M Chen (Journal for ImmunoTherapy of Cancer, 2023)
Background Circulating transforming growth factor-β (TGF-β)-specific T cells that recognize TGF-β-expressing immune regulatory cells have been described in patients with cancer. TGF-β-derived peptide vaccination modulates the tumor microenvironment and has shown clinical effects in animal models of pancreatic cancer (PC). TGF-β-expressing regulatory cells are especially elevated in PC and may prevent the clinical response to immune checkpoint inhibitors (ICIs). Thus, in the present study we investigated the significance of TGF-β-specific T-cell immunity in patients with PC treated with ICI combined with radiotherapy in a randomized phase 2 study (CheckPAC).Methods Immune responses to a TGF-β-derived epitope entitled TGF-β-15 as well as epitopes from Clostridium tetani (tetanus) and influenza were measured in peripheral blood mononuclear cells (PBMCs) with interferon-ɣ enzyme-linked immunospot assays. PBMCs were isolated before and after treatment. Correlations between immune response data and clinical data were evaluated with parametric and non-parametric statistical methods. Survival was analyzed with univariate and multivariate Cox-regression. TGF-β-15 specific T cells were isolated and expanded and examined for recognition of autologous regulatory immune cells by flow cytometry.Results PBMCs from 32 patients were analyzed for immune responses to the TGF-β-derived epitope entitled TGF-β-15. Patients with a strong TGF-β-specific immune response at treatment initiation had longer progression-free and overall survival, compared with patients with a weak or no TGF-β-specific immune response. This remained significant in multivariate analysis. Patients with weak and strong TGF-β-specific responses displayed similar responses towards viral antigens. Furthermore, we show that TGF-β-specific T cells from a clinical responder specifically reacted to and lysed autologous, regulatory immune cells. Finally, mimicking a TGF-β-15 vaccination, we showed that repeated stimulations with the TGF-β-15 epitope in vitro enhanced the immune response to TGF-β-15.Conclusion A strong TGF-β-15 specific immune response was associated with clinical benefit and improved survival after ICI/radiotherapy for patients with PC. Importantly, the lack of TGF-β-specific T cells in some patients was not caused by a general immune dysfunction. TGF-β-specific T cells recognized regulatory immune cells and could be introduced in vitro in patients without spontaneous responses. Taken together, our data suggest that combining TGF-β-based vaccination with ICI/radiotherapy will be beneficial for patients with PC.